PsycEXTRA Dataset 2005
DOI: 10.1037/e464192006-001
|View full text |Cite
|
Sign up to set email alerts
|

Behind the Scenes: Patient Safety in the Operating Room and Central Materiel Service During Deployments

Abstract: The United States Army perioperative nurses face unique patient care situations during overseas deployments. In this report, the experiences at the U.S. Army's 28 th Combat Support Hospital in Iraq are described. The lessons learned from these situations can assist in patient safety in future operations. The challenges to the nursing staff of performing "housekeeping" tasks while simultaneously accomplishing a number of other patient care tasks are reviewed. The surgical suite structural requirements for the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…22,23 Despite reports of challenges to maintain an adequate sterile environment within ORs under austere conditions, the limited environmental sampling of OR surfaces in an Afghanistan field hospital did not reveal gram-negative bacteria contamination. 24 Comparative environmental sampling in modular field-type ORs that are used in the deployed combat environment and fixed-facility ORs in the United States also demonstrated no significant contamination. Although studies have demonstrated a correlation between length of surgery and aerosolization of bacteria during wound care of burn patients with MRSA infections, we did not show appreciable aerosolization of bacteria during surgery, except maybe in the case of burn patients.…”
Section: Environmental Soilmentioning
confidence: 98%
“…22,23 Despite reports of challenges to maintain an adequate sterile environment within ORs under austere conditions, the limited environmental sampling of OR surfaces in an Afghanistan field hospital did not reveal gram-negative bacteria contamination. 24 Comparative environmental sampling in modular field-type ORs that are used in the deployed combat environment and fixed-facility ORs in the United States also demonstrated no significant contamination. Although studies have demonstrated a correlation between length of surgery and aerosolization of bacteria during wound care of burn patients with MRSA infections, we did not show appreciable aerosolization of bacteria during surgery, except maybe in the case of burn patients.…”
Section: Environmental Soilmentioning
confidence: 98%